2016
DOI: 10.1038/srep28015
|View full text |Cite
|
Sign up to set email alerts
|

The feeding habit of sea turtles influences their reaction to artificial marine debris

Abstract: Ingestion of artificial debris is considered as a significant stress for wildlife including sea turtles. To investigate how turtles react to artificial debris under natural conditions, we deployed animal-borne video cameras on loggerhead and green turtles in addition to feces and gut contents analyses from 2007 to 2015. Frequency of occurrences of artificial debris in feces and gut contents collected from loggerhead turtles were 35.7% (10/28) and 84.6% (11/13), respectively. Artificial debris appeared in all g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…, Fukuoka et al. ). Plastic items can block the digestive system of turtles resulting in the death of the individual (Mascarenhas et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Fukuoka et al. ). Plastic items can block the digestive system of turtles resulting in the death of the individual (Mascarenhas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Macroalgae dominant. Macroalga is consumed most abundantly in the following sub-regions: Pacific N Central (mean = 96.0%; SE = 1.9; n = 6; e.g., Arthur and Balazs 2008;Balazs et al 1987), Atlantic E (mean = 62.5; SE = 7.5; n = 2; e.g., Hancock et al 2018), Atlantic SW (mean = 59.5%; SE = 13.9; n = 9) especially tropical areas (e.g., Reisser et al 2013), Pacific S Central (mean = 58.5; SE = 41.5; n = 2; e.g., Piovano et al 2020;Balazs 1983), Pacific NW (mean = 52.5%; SE = 9.4; n = 4), Indian SE (mean = 51.7%; SE = 14.2; n = 5; e.g., Shimada et al 2014;Fukuoka et al 2016), Pacific E (mean = 49.4%; SE = 7.7; n = 18; e.g. Seminoff et al 2002;Arthur and Balazs 2008;Carrión-Cortez et al 2010;Quiñones et al 2010), and Atlantic NW (mean = 34.1%, SE = 7.7; n = 19) especially high in temperate areas (e.g., Holloway-Adkins and Hansiak 2017).…”
Section: Global Review Of Green Turtle Dietmentioning
confidence: 99%
“…We conclude that green turtle omnivory may be partly driven by water temperature, and we present the first quantitative evidence that temperature may be an important driver of diet in green turtles at a global scale, especially where the diet includes gelatinous macrozooplankton (in particular, jellyfish and salps). Gelatinous macrozooplankton featured most prominently at oceanic and extreme-latitude sites in the Pacific and Atlantic, ranging from 40% in the Pacific NW (Fukuoka et al 2016); 30-73% in the oceanic Pacific NC (Parker et al 2011;Wedemeyer-Strombel et al 2015); 38-72% along the Pacific E coastline (Seminoff et al 2006;Amorocho and Reina 2007;Quiñones et al 2010;Lemons et al 2011;Jiménez et al 2017); and 40-59% in the Atlantic SW (Bugoni et al 2003;González Carman et al 2014). A feature shared by all these sites appears to be much cooler water temperatures (< 20 °C) during all or part of the year.…”
Section: Sst As a Driver Of Variation In Green Turtle Dietmentioning
confidence: 99%
“…It has been suggested that animals feed on plastics because they look and smell like prey (Boerger et al, 2010;Fukuoka et al, 2016;Procter et al, 2019;Savoca et al, 2017).…”
Section: Introductionmentioning
confidence: 99%